A Different Definition of “Boob-Tube”: What Dr. Catherine Gale, of The Avengers, Taught Women - Robin Redmon Wright (Adult Education Research Conference, 2006)
This paper summarizes a qualitative research project exploring the impact of the first feminist television character, Cathy Gale, of the 1962-64 British television program, The Avengers. Contemporaneous British women viewers reveal how Gale’s character helped them reject traditional roles, incorporate the character’s strengths, and seek out other feminist role models.
Keywords: Feminist; television; Avengers; adult learning; transformational